The Effect of Health Education on Mothers’ Knowledge, Attitudes, and Practices in Early Detection of Toddler Growth and Development - Sami Alarsan (Journal of Health Innovation and Environmental Education, 2024)
Purpose of the study: This study aims to assess the effectiveness of health education in improving mothers’ knowledge, attitudes, and practices regarding early detection of toddler growth and development at Posyandu Mawar, Puskesmas Arosbaya. The study focuses on maternal ability to monitor developmental milestones to prevent long-term developmental delays. Methodology: A pre-experimental one-group pretest-posttest design was used. Thirty mothers of toddlers aged 12–36 months participated. Data were collected using structured questionnaires, direct observation, demonstrations, and interactive health education sessions. Analysis was performed with the Wilcoxon signed-rank test (α = 0.05) to measure improvements in knowledge, attitudes, and practices. Main Findings: After the health education intervention, mothers’ knowledge improved with 60% achieving good knowledge and 40% sufficient. Positive attitudes increased from 23.3% to 53.3%. Practices also improved, with 50% demonstrating good practices and 50% fair practices. Statistical tests confirmed significant improvements (p < 0.05) in all three domains. Novelty/Originality of this study: This study integrates cognitive, affective, and psychomotor domains by simultaneously evaluating knowledge, attitudes, and practices. It positions mothers as the main subjects, applying interactive lectures, discussions, and demonstrations in a primary healthcare setting. The approach provides comprehensive insights into health education effectiveness in real-world community contexts, informing future promotive and preventive programs.